PENGARUH KUALITAS PELAYANAN DAN PENETAPAN HARGA TERHADAP KEPUASAN KONSUMEN PADA HOTEL INNA PARAPAT GIRSANG SIPANGANBOLON - Manurung, Juni Yanti; Heriyanto, Meyzi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research was conducted at Hotel Inna Parapat Girsang Sipanganbolon. The purpose of this study was to determine the effect of service quality and pricing on consumer satisfaction at the Hotel Inna Parapat Girsang Sipanganbolon. The influence of service quality and pricing as independent variables (X1, X2) while consumer satisfaction as the dependent variable (Y). The problem in this research is the reduction in the number of consumers in the last  two years, the number of consumers staying overnight is decreasing. It can be seen from the data of consumer visits and the table of scores given by consumers. The sample of this study was taken as many as 100 respondents from the population which was calculated using the Slovin formula. The data obtained from the results of the questionnaire and then processed and then tested with statistics through the SPSS program. From the results of the tests carried out, it shows that the influence of service quality and pricing has a positive and significant effect on customer satisfaction at the Inna Parapat Girsang Sipanganbolon Hotel.        Keywords : Service Quality, Pricing and Consumer Satisfaction